(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
It has been used for many years and can be defined as the compensatedinclusion of a branded product or brand identifiers, through audio and/orvisual means within mass media programming (films and broadcast programmes) forpromotional purposes. The survey method entailed that respondents had toobserve a series of scenes from a film clip containing product placements;thereafter they were required to complete a questionnaire. Two hundredrespondents, between the ages of 18 to 24 participated in this survey. Resultsindicated that their ability to recall prominently placed products is greaterthan their ability to recall subtly placed products. It further indicates thata principal actor using a brand in a film or broadcast programmes does notnecessarily influence consumers’ affective behaviour. It is suggested thatproduct placements will become a strategic and viable marketing option in themobile environment for targeting specific groups. Advertising companies seekmore venues for products. From these findings it can be concluded that ifmarketers and advertisers consider product placements as an integratedmarketing communication vehicle, they must request that their brands are placedprominently in a film and broadcast programmes to ensure maximum exposure andgreater awareness among consumers. The results also provide useful insight tomedia planners as to whether product placement is effective when the principalactor uses it.